If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11+6t=6t+9+2
We move all terms to the left:
11+6t-(6t+9+2)=0
We add all the numbers together, and all the variables
6t-(6t+11)+11=0
We get rid of parentheses
6t-6t-11+11=0
We add all the numbers together, and all the variables
=0
t=0/1
t=0
| (9)(3x)-1=0 | | 5-2l=-5 | | 34+7l=111 | | 15-d=23 | | 4=v/3-1 | | t-1,t=7 | | -3x+8=-5x-18 | | 3-(x+4)=5x+8 | | -17k-20=2(-9k-10)+16 | | 19k+2=21 | | 10=u-1 | | -13u+3=-10u+12 | | 19k+2=22 | | 4n-8=3n+8 | | T-4=5t+3t-32 | | 1(10k-16)+11=-2 | | 2(x+4)=16-6x* | | y+12=42 | | 80=0.25x(50+45) | | F(n)=24 | | 1=3+p/8 | | f/6-20=-22 | | r-76=67 | | 6+14n=-14-17+14n | | 4y,y=3 | | x-4x3=24 | | .25x-5=10-x | | 25=5m-10 | | 12-5e=-28 | | -21=-3+u/3 | | 6t+12=-20+12t-10 | | 3t-510=450 |